Hubungan Antara Konsep Diri Akademik Dengan Kemandirian Belajar Siswa - Faradis, Tazkiyah; Pratikto, Herlan; Suhadianto (BULLET : Jurnal Multidisiplin Ilmu, 2024)
Academic self-concept is students' perceptions or thoughts about their abilities in the academic field which are formed through experiences with the environment. Learning independence is an act of controlling the learning process where students take their own initiative in planning, implementing and evaluating their learning experiences taken from various learning sources. This research aims to determine the relationship between academic self-concept and student learning independence. This research uses quantitative correlational methods. The population in this study was all 285 class IX students at MTS Darul Ulum Sidoarjo. Sampling in this study used the proportional random sampling method and was taken according to the Slovin formula with an error tolerance of 5% and was collected from 166 students. Data were collected in this research by distributing questionnaires, with an academic self-concept scale and a learning independence scale. Data analysis in this study used the Pearson Product Moment correlation test technique and obtained r = 0.820 with a significance of 0.000 (p<0.05). This means that the hypothesis in this study assumes there is a positive relationship between academic self-concept and learning independence in class IX at MTS Darul Ulum Sidoarjo was accepted. This means that the higher a student's academic self-concept, the higher their learning independence.